MRI Findings in Patients Considered High Risk for Pelvic Floor Injury Studied Serially Post Vaginal Childbirth - Miller, Janis M. (2010)
OBJECTIVE: To characterize pelvic floor injury after vaginal childbirth with serial MRI. METHODS: 3T MR images were obtained early (1-month) and late (7-months) after childbirth in 19 women with risk factors for pelvic floor injury. All received multiplanar intermediate-weighted sequences and 11 had fluid sensitive sequences. MR images were evaluated for levator edema and tears, and pubic abnormalities. RESULTS: Three had unilateral high-grade tears, three had unilateral low grade tears, one had bilateral high and low-grade tears of the levator ani muscles. All tears were focal at the pubis. Levator edema was present in all on initial imaging and resolved at follow-up. Six had bone marrow edema; five with fracture line. None showed a pattern indicating nerve damage separate from muscle tears. CONCLUSION: MRI showed focal levator ani muscle tears at the pubis with bone marrow edema and fracture in patients at risk for pelvic floor injury.